Effect Of An Activity-Based Learning In Teaching Arabic Paragraph Writing To AFL Learners - Sathikulameen, A.; Zubair, K.M.A. Ahamed; Nadwi, A. Abdul Hai Hasani; Ahamedullah, M.; Ibrahim, A.M. Ali (Ijaz Arabi Journal of Arabic Learning, 2023)
This paper examined an activity-based approach that fosters Arabic paragraph writing of AFL (Arabic as a Foreign Language) undergraduate learners at The New College, Chennai, India. A total of 25 learners were chosen for this study. They participated in the selected activities to improve their paragraph writing skills in Arabic. The chosen group showed signs of progress in this activity-based approach. For this study, the data were collected through quantitative and qualitative questionnaires before and after the activities. The results showed that the activity-based approach brought about potential changes in their paragraph writing skills. This study has both pedagogical and policy-level implications for fostering paragraph writing skills. The pedagogical implications emphasize the value of learner-centered tactics in improving Arabic paragraph writing abilities, and the policy-level implications underline the need to introduce learner-centric language teaching methodologies in higher education.